Digital Strategic Alignment in Smart Ecosystems: A Synthesis of Strategic Capabilities and Emerging Technologies - Mahadi Pardede; Agus Rahayu; Vanessa Gaffar (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: The rapid development of AI, IoT, Big Data, and Blockchain is reshaping business and management. While research has emphasized technical aspects, less is known about their strategic implications. This study explores how firms adapt managerial strategies within smart ecosystems.Purpose: The study examines how organizations adjust strategic management to sustain competitiveness amid digital transformation, focusing on managerial perspectives in areas such as AI governance, data-driven decisions, and ecosystem collaboration.Design/Methodology/Approach: A Systematic Literature Review (2010–2024) was conducted using peer-reviewed sources. Selected studies addressed strategic management excluding purely technical works and were categorized into AI strategy, Big Data analytics, Blockchain governance, and business models.Findings/Result: Digital technologies enhance agility and innovation but pose challenges in cybersecurity, regulation, and interoperability. The study applies Dynamic Capabilities, Resource-Based View, and Ecosystem Perspectives, identifying gaps in AI governance, SME digital adoption, and sustainability.Conclusion: Five strategic priorities emerge: predictive AI, real-time Big Data insights, secure Blockchain applications, robust cybersecurity, and dynamic capabilities. Firms leveraging collaborative and platform-based strategies adapt more effectively, though SMEs face significant constraints.Originality/Value (State of the art): Unlike prior research emphasizing technical dimensions, this study highlights strategic implications of digital technologies for competitive advantage and sustainability. The SLR reveals key trends, challenges, and opportunities, offering actionable insights for managers and policymakers. Keywords:  artificial intelligence, big data, blockchain, smart ecosystems, strategic management